2021
DOI: 10.3389/fmolb.2021.626837
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Hydropathy of Amino Acid Side Chain in a Protein Environment by Investigating the Structural Changes of Water Molecules Network

Abstract: Assessing the hydropathy properties of molecules, like proteins and chemical compounds, has a crucial role in many fields of computational biology, such as drug design, biomolecular interaction, and folding prediction. Over the past decades, many descriptors were devised to evaluate the hydrophobicity of side chains. In this field, recently we likewise have developed a computational method, based on molecular dynamics data, for the investigation of the hydrophilicity and hydrophobicity features of the 20 natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 50 publications
1
42
0
Order By: Relevance
“…They defined four groups of amino acids by applying a principal component analysis and distinguish between negatively charged, positively charged, polar, and nonpolar amino acids. Accordingly, comparing the amino acid content of investigated proteins in this study, it is confirmed that hemoglobin and AFP III consists mainly out of hydrophobic amino acids whereas in BSA and Lysozyme most prevalent amino acids belong to the charged group (Di Rienzo et al, 2021).…”
Section: A N Na Nsupporting
confidence: 67%
“…They defined four groups of amino acids by applying a principal component analysis and distinguish between negatively charged, positively charged, polar, and nonpolar amino acids. Accordingly, comparing the amino acid content of investigated proteins in this study, it is confirmed that hemoglobin and AFP III consists mainly out of hydrophobic amino acids whereas in BSA and Lysozyme most prevalent amino acids belong to the charged group (Di Rienzo et al, 2021).…”
Section: A N Na Nsupporting
confidence: 67%
“…As exhibited in Figure , compared with the bare GCE and AuNPs/PEDOT/GCE, pep1/AuNPs/PEDOT/GCE showed much less DPV signal suppression associated with nonspecific protein adsorption in all of the tested single protein solutions, including negatively charged BSA (Figure , a0–a3), positively charged Lyz (Figure , b0–b3), and electrically neutral protein Mb (Figure , c0–c3). This result illustrated the superior ability of pep1/AuNPs/PEDOT/GCE to resist nonspecific protein adsorption, thanks to the presence of the designed peptide, which is neutral in charge and has good hydrophilicity , as shown in Figure S1C.…”
Section: Resultsmentioning
confidence: 73%
“…Hydrophilicity and neutral charge are two key parameters for the designed peptides to possess the antifouling property. ,, Hence, the hydrophilicity of the designed peptide was investigated by the peptide property calculator and water contact angle test, as presented in Figure S1. The hydropathy distribution image (Figure S1A) clearly shows that most of the amino acids of pep1 (chemical formula shown in Figure S1B) are hydrophilic. The measured water contact angles of bare GCE and the AuNPs/PEDOT and pep1/AuNPs/PEDOT modified electrode surfaces (Figure S1C) are 61.92, 66.43, and 28.54°, respectively, which indicated that modification of the peptide can significantly enhance the hydrophilicity of the electrode surface, proving the strong hydrophilicity of the designed peptide.…”
Section: Resultsmentioning
confidence: 99%
“…This is at the core of the development of the 2D Zernike polynomial expansion [ 8 ] as a method to find the protein-protein binding regions. This method could in principle be adapted to other properties (such as electrostatics or hydrophobicity) besides curvature since they can be described with numerical values that can be assigned to each surface point [ 25 , 26 ], and the Zernike expansion can be applied to any function. Nonetheless, in this work the algorithm is used to maximize the information concerning only the overall shape of the molecule.…”
Section: Introductionmentioning
confidence: 99%